Determining energy, exergy and enviroeconomic analysis of stand-alone photovoltaic panel under harsh environment condition: Antarctica Horseshoe-Island cases - Arslan, Erhan; Küçük, Furkan Ali; Biçer, Çetin; Özsoy, Burcu (Elsevier BV, 2024)
It is considered that some of the energy needs of the Turkish Science Base, which will be established on the Antarctic Horseshoe Island, will be supplied from solar energy. In this study, the performance of the PV panel was experimentally tested on the Antarctic Horseshoe Island. Energy, exergy and enviroeconomic analysis of the PV panel were performed. In the experiments carried out for three days, the energy efficiency was determined as 5.40%, 7.39% and 11.35%, respectively. The exergy efficiencies were calculated as 4.53%, 6.58% and 10.25%, respectively. At the end of three experiments, the amount of CO 2 blocked to the atmosphere was determined as 3.06 kg on average. The study used meteorological parameters (solar radiation, wind speed, humidity, and ambient air temperature) and other data (current -voltage, panel surface temperature, convection and radiation heat transfer coefficients, sky temperature, total heat transfer coefficient, total heat loss and exergy destruction) that can only be calculated using these variables to estimate the electrical efficiency of the PV module. This was achieved using the multilayer perceptron and decision tree method. The process of approximating the values estimated by statistical evaluations to the values calculated experimentally for energy efficiency was found to have error rates of 5.6% and 12.5%, respectively.